Avaliação da intensidade de dor e da funcionalidade no pós-operatório recente de cirurgia cardíaca - Borges, Juliana Bassalobre Carvalho [UNESP]; Ferreira, Daniele Leandra Mengue de Paula [UNESP]; Carvalho, Sebastião Marcos Ribeiro de; Martins, Antonio Sérgio [UNESP]; Andrade, Rubens Ramos de [UNESP]; Silva, Marcos Augusto de Moraes [UNESP] (Sociedade Brasileira de Cirurgia Cardiovascular, 2006)
OBJETIVO: Avaliar a intensidade de dor e o nível de funcionalidade em pacientes submetidos à cirurgia cardíaca nos períodos pré-operatório, 7º pós-operatório e alta hospitalar, relacionando-os entre si. Relacionar funcionalidade com: sexo, faixa etária, primeira cirurgia cardíaca ou reoperação, uso de circulação extracorpórea (CEC), tipo de cirurgia e acompanhamento fisioterapêutico. MÉTODO: Foram estudados 41 pacientes que realizaram cirurgia cardíaca eletiva por toracotomia médio-esternal (TME) no HC da Faculdade de Medicina de Botucatu/UNESP. A intensidade de dor foi avaliada pela escala de VAS e a funcionalidade, pela escala MIF (medida de independência funcional) no domínio físico. RESULTADOS: A intensidade de dor mais elevada foi no 7º pós-operatório comparado com os momentos pré-operatório e alta. No pré-operatório, não houve índice de dor; na alta, a intensidade mediana foi 3 (dor moderada). Os níveis mais elevados de perda funcional ocorreram no 7º pós-operatório, quando comparados com os escores totais do pré-operatório e da alta. Verificou-se correlação significativa entre dor e funcionalidade, demonstrando que o decréscimo do nível de dor entre o 7º pós-operatório e a alta contribuiu para a elevação dos níveis funcionais. CONCLUSÃO: As avaliações realizadas no pré-operatório proporcionaram resultados preditivos a serem alcançados. As avaliações realizadas no 7º pós-operatório e na alta possibilitaram a classificação dos pacientes de acordo com perdas e ganhos, indicando aqueles que necessitavam de maior cuidado e treinamento em suas capacidades.

OBJECTIVE: To evaluate, in patients submitted to heart surgery, the intensity of pain and the level of functionality during the preoperative period, on the 7th postoperative day and at hospital discharge. A secondary objective was to evaluate any possible relationship between pain and functionality taking into account the following variables: gender, age, first heart surgery or re-interventions, use of cardiopulmonary bypass (CPB), type of surgery and physiotherapeutic follow-up. METHOD: Forty-one patients who had undergone elective heart surgery at the Teaching Hospital of Botucatu/UNESP were studied. Pain intensity was measured using the VAS scale and functionality by the FIM scale (Functional Independence Measure) in the physical domain. RESULTS: It was observed that the intensity of pain was higher on the 7th postoperative day when compared with the preoperative period and at hospital discharge. No pain rating score was shown in the preoperative period, while a median pain intensity of 3 (moderate pain), was noted at hospital discharge. The highest levels of functional loss occurred on the 7th postoperative day compared to the total scores obtained in the preoperative period and at hospital discharge. A significant correlation between pain and functionality was observed; a decrease in level of pain between the 7th postoperative day and hospital discharge contributed to an increase in the functional levels. CONCLUSION: The evaluations performed in the preoperative period provided predictable results. The evaluations carried out on both the 7th postoperative day and at hospital discharge enabled a classification of patients according to their functional gain or loss, which contributed to identify those who require more care and training of their abilities.
Pain intensity and postoperative functional assessment after heart surgery
Keywords: Procedimentos cirúrgicos cardíacos; Dor; Dor pós-operatória; Medição da dor; Reabilitação; Cardiac surgical procedures; Pain; Pain, postoperative; Pain measurement; Rehabilitation